2021
DOI: 10.3390/ijerph18126289
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Sleep Disturbances and Psychological Strain for Hospital Staff Working during the COVID-19 Pandemic

Abstract: Hospital staff members reported increased stress-related workload when caring for inpatients with COVID-19 (“frontline hospital staff members”). Here, we tested if depression, anxiety, and stress were associated with poor sleep and lower general health, and if social support mediated these associations. Furthermore, we compared current insomnia scores and general health scores with normative data. A total of 321 full-time frontline hospital staff members (mean age: 36.86; 58% females) took part in the study du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 84 publications
0
17
0
1
Order By: Relevance
“…For instance, the high levels of stress experienced by nurses due to caring for COVID‐19 patients has been reported and associated with separation from family, sleep deprivation, lack of preparedness and increased workloads due to higher health care demands and new policies and procedures to follow (e.g., Huang et al, 2020 ). The high levels of depression, anxiety and stress resulting from caring for COVID‐19 patients have also been found to be associated with high insomnia and low general health (e.g., Abdoli et al, 2021 ). Furthermore, several studies have demonstrated the adverse impact of the pandemic on health care workers such as burnout, stress, depression and anxiety, with higher prevalence rates of anxiety and depression found among nurses compared with other health care workers (Pappa et al, 2021 ; Wang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the high levels of stress experienced by nurses due to caring for COVID‐19 patients has been reported and associated with separation from family, sleep deprivation, lack of preparedness and increased workloads due to higher health care demands and new policies and procedures to follow (e.g., Huang et al, 2020 ). The high levels of depression, anxiety and stress resulting from caring for COVID‐19 patients have also been found to be associated with high insomnia and low general health (e.g., Abdoli et al, 2021 ). Furthermore, several studies have demonstrated the adverse impact of the pandemic on health care workers such as burnout, stress, depression and anxiety, with higher prevalence rates of anxiety and depression found among nurses compared with other health care workers (Pappa et al, 2021 ; Wang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, to decrease the spread of the virus and prevent further deaths and severe cases of infection, national governments, advised by health authorities, imposed confinements. To illustrate this, health authorities temporarily legislated to close borders, schools, universities, sports events, religious and cultural centers, and disallow gatherings in open spaces [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…To calculate the direct and indirect effects of past non-suicidal self-injury on current non-suicidal self-injury via sleep disturbances, we again followed Rudolf and Müller [ 49 ] and Abdoli et al [ 50 ]. Table 8 reports the equation.…”
Section: Resultsmentioning
confidence: 99%